Quality of Life of Chronic Hepatitis B Patients Consuming Nucleoside Analog: A Case-Control Clinical Study in Indonesia - Natasya Ariesta Selyardi Putri; R. Haryanto Aswin; Izzatul Fithriyah; Ummi Maimunah; Yoshio Yamaoka; Muhammad Miftahussurur (Biomolecular and Health Science Journal, 2022)
Introduction: Chronic hepatitis B raises serious concern due to its high morbidity, such as cirrhosis and hepatocellular carcinoma, and mortality from 267 per 100,000 person-years. Up to now, medical therapy that successfully eradicates the hepatitis B virus is not available. Therapy is given in the long term for suppressing viral replication and disease progression. Nucleoside analog (NA) is a medication that is consumed orally once a day for years. Previous studies showed that patients who were treated with NA had a different quality of life (QoL) compared to naïve patients. This research aimed to analyze the QoL of chronic hepatitis B patients who consumed NA by comparing it with naïve patients at Dr. Soetomo General Academic Hospital Surabaya. Methods: Subjects were recruited consecutively from chronic hepatitis B patients at Dr. Soetomo General Academic Hospital Surabaya during 9 February – 31 May 2021. Data about sociodemographic characteristics, hepatitis B therapy history, and QoL were gained by using the SF-36 questionnaire and medical records. Subjects were divided into NA and naïve groups which responses underwent an analytical comparison. Results: NA group had significantly higher QoL in a physical component score (PCS) and mental component score (MCS), with physical functioning (PF), role limitations due to physical health (RP), role limitations due to emotional problems (RM), energy/fatigue (VT), emotional well-being (MH), social functioning (SF), and general health perception (GH) subscales having p<0.05Conclusion: The QoL of patients who were treated with NA was significantly higher than that of naïve patients in terms of physical and mental components.